#### Answer

$4x^{2}-5$

#### Work Step by Step

$(2x-\sqrt 5)(2x+\sqrt 5)=(2x)^{2}-(\sqrt 5)^{2}=4x^{2}-5$

Published by
Pearson

ISBN 10:
0321726391

ISBN 13:
978-0-32172-639-1

$4x^{2}-5$

$(2x-\sqrt 5)(2x+\sqrt 5)=(2x)^{2}-(\sqrt 5)^{2}=4x^{2}-5$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.